Hydrogen Exchange Studies and Proton Transfer in β Iron(III) Oxyhydroxide - K.J. Gallagher; D.N. Phillips (CHIMIA)
The kinetics of hydrogen exchange between tritiated water and /3-FcOOH crystals have been found to be dependent on pH in the alkaline region but independent in the acid region. The exchange formally obeyed a diffusion controlled law, and yielded the same activation energy 97 joules mole-1 (23 kcal mole-1) in both the alkaline and acid regions. The difference in kinetic behaviour on increasing pH in the alkaline region was attributed to a decrease in Do, the pre-exponential factor in the self- diflfusion coefficient.